PERAN ICE BREAKING DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PPKN KELAS V DI SEKOLAH SD NEGERI RAPPOJAWA NO.71 MAKASSAR - Waalidain, Ridhol; Martini; Hasan, Salim; Kade, Samsuddin; Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the role of ice breaking in improving the learning motivation of fifth-grade students in Civics Education (PPKn) at SD Negeri Rappojawa No. 71 Makassar, as well as to identify the supporting and inhibiting factors in its implementation. This study employed a qualitative approach using a descriptive research design. Data were collected through observation, interviews, and documentation, and were analyzed using data reduction, data presentation, and conclusion drawing. The results showed that the implementation of ice breaking was able to improve students' learning motivation. Students became more enthusiastic, active, focused, and engaged in the learning process. In addition, ice breaking created an enjoyable learning atmosphere that facilitated teachers in delivering the learning materials. The supporting factors included students' interest, teachers' creativity, the use of varied teaching methods, and the availability of learning media. Meanwhile, the inhibiting factors were differences in students' characteristics, students' difficulty in regaining focus after ice breaking activities, and teachers' limited references to ice breaking activities.